A paired kidney analysis on the impact of pre-transplant anti-HLA antibodies on graft survival. Issue 6 (25th October 2018) - Michielsen, Laura A; Wisse, Bram W; Kamburova, Elena G; Verhaar, Marianne C; Joosten, Irma; Allebes, Wil A; van der Meer, Arnold; Hilbrands, Luuk B; Baas, Marije C; Spierings, Eric; Hack, Cornelis E; van Reekum, Franka E; et al.
Abstract: Background: Pre-transplant donor-specific anti–human leucocyte antigen (HLA) antibodies (DSAs) are associated with impaired kidney graft survival while the clinical relevance of non-donor-specific anti-HLA antibodies (nDSAs) is more controversial. The aim of the present paired kidney graft study was to compare the clinical relevance of DSAs and nDSAs. Methods: To eliminate donor and era-dependent factors, a post hoc paired kidney graft analysis was performed as part of a Dutch multicentre study evaluating all transplantations between 1995 and 2005 with available pre-transplant serum samples. Anti-HLA antibodies were detected with a Luminex single-antigen bead assay. Results: Among 3237 deceased donor transplantations, we identified 115 recipient pairs receiving a kidney from the same donor with one recipient being DSA positive and the other without anti-HLA antibodies. Patients with pre-transplant DSAs had a significantly lower 10-year death-censored graft survival (55% versus 82%, P=0.0001). We identified 192 pairs with one recipient as nDSA positive (against Class I and/or II) and the other without anti-HLA antibodies. For the patients with nDSAs against either Class I or II, graft survival did not significantly differ compared with patients without anti-HLA antibodies (74% versus 77%, P = 0.79). Only in patients with both nDSAs Class I and II was there a trend towards a lower graft survival (58%, P = 0.06). Lastly, in a small group of 42 recipient pairs, 10-year graft survival in recipients with DSAs was 49% compared with 68% in recipients with nDSAs (P=0.11). Conclusion: This paired kidney analysis confirms that the presence of pre-transplant DSAs in deceased donor transplantations is a risk marker for graft loss, whereas nDSAs in general are not associated with a lower graft survival. Subgroup analysis indicated that only in broadly sensitized patients with nDSAs against Class I and II, nDSAs may be a risk marker for graft loss in the long term.